2023
DOI: 10.1186/s13045-023-01436-2
|View full text |Cite
|
Sign up to set email alerts
|

Emerging evidence and treatment paradigm of non-small cell lung cancer

Abstract: Research on biomarker-driven therapy and immune check-point blockade in non-small cell lung cancer (NSCLC) is rapidly evolving. The width and depth of clinical trials have also dramatically improved in an unprecedented speed. The personalized treatment paradigm evolved every year. In this review, we summarize the promising agents that have shifted the treatment paradigm for NSCLC patients across all stages, including targeted therapy and immunotherapy using checkpoint inhibitors. Based on recent evidence, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 133 publications
0
14
0
Order By: Relevance
“…Third-generation EGFR-TKIs have greater BBB penetration than first- and second-generation EGFR-TKIs, and are considered standard treatment for patients with CNS metastasis. 21 , 22 Phase III studies have reported CNS ORRs of osimertinib and aumolertinib of 57% and 62%, respectively, and CNS PFSs of furmonertinib, and aumolertinib of 29.0 and 20.8 months, respectively. 8 , 9 , 10 However, these findings were generated from prespecified subgroup analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Third-generation EGFR-TKIs have greater BBB penetration than first- and second-generation EGFR-TKIs, and are considered standard treatment for patients with CNS metastasis. 21 , 22 Phase III studies have reported CNS ORRs of osimertinib and aumolertinib of 57% and 62%, respectively, and CNS PFSs of furmonertinib, and aumolertinib of 29.0 and 20.8 months, respectively. 8 , 9 , 10 However, these findings were generated from prespecified subgroup analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the development of new ICIs is imperative. The number of approved cancer treatment drugs based on ICIs has been increasing, and it is also an enduring research hotspot [ 78 ]. Immunotherapy drugs targeting T cell immunoreceptors with immunoglobulin and ITIM domains, the lymphocyte activation gene 3, T cell immunoglobulin, mucin-domain 3 and immune checkpoint siglec-15 are in clinical trials or under development [ 74 , 79 ].…”
Section: Discussion and Prospectmentioning
confidence: 99%
“…In recent years, targeted therapy and immunotherapy have emerged and shifted the treatment paradigm for NSCLC patients across all stages. Specially, in patients without driver gene mutations, immunotherapy has opened a new therapeutic window [ 2 , 3 ]. For instance, studies have revealed that immune checkpoint inhibitors (ICIs) represented by PD-1/PD-L1 antagonists significantly prolong the overall survival of advanced NSCLC patients alone or in combination with other anticancer agents [ [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%